2010
DOI: 10.2495/hpsm100071
|View full text |Cite
|
Sign up to set email alerts
|

Durability study of lightweight concrete material made from date palma seeds (DPS)

Abstract: Libya is one of the largest producers of dates from date palm, generating about 60000 tonnes of date palm seeds (DPS) annually. This large amount of seeds led to studies into the possible use as aggregates in lightweight concrete for some special structures. The utilization of DPS as aggregate in concrete provides a good solution as alternative aggregate to the stone aggregate. It has been recognized that, DPS can be used as coarse aggregate in structural lightweight concrete industry. For any structure member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Pulverized ground date pits are being used on a small scale on dirt roads as a type of road base gravel [27]. Almograbi [28] has reported that the large quantity of date palm seed waste has led to studies focusing on the possible use of this waste as aggregates in special structural lightweight concrete. Date palm seeds are lightweight, making the resulting concrete also lightweight.…”
Section: Introductionmentioning
confidence: 99%
“…Pulverized ground date pits are being used on a small scale on dirt roads as a type of road base gravel [27]. Almograbi [28] has reported that the large quantity of date palm seed waste has led to studies focusing on the possible use of this waste as aggregates in special structural lightweight concrete. Date palm seeds are lightweight, making the resulting concrete also lightweight.…”
Section: Introductionmentioning
confidence: 99%